Further evidence on the (in-) efficiency of the U.S. housing market - Felix Schindler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Extending the controversial findings from relevant literature on testing the efficient market hypothesis for the U.S. housing market, the results from the monthly and quarterly transaction-based Case-Shiller indices from 1987 to 2009 provide further empirical evidence on the rejection of the weak-form version of efficiency in the U.S. housing market. In addition to conducting parametric and non-parametric tests, we apply technical trading strategies to test whether or not the inefficiencies can be exploited by investors earning excess returns. The empirical findings suggest that investors might be able to obtain excess returns from both autocorrelation- and moving average-based trading strategies compared to a buy-and-hold strategy.
Keywords: G12; G14; G15; R31; 330; Housing market; weak-form market efficiency; random walk hypothesis; variance ratio tests; runs test; trading strategies; Wohnungsmarkt; Effizienzmarktthese; Random Walk; Schätzung; USA